Gestational Diabetes Mellitus and Iron Deficiency Anemia - Neslihan Yerebasmaz; Şeyma Asiltürk; Erdem Fadıllıoğlu; Özlem Şengül; Serdar Yalvaç; Ömer Kandemir (Medical Network, 2016)
OBJECTIVE: To determine whether gestational diabetes mellitus is influenced by the presence of iron deficiency anemia in early pregnancy. STUDY DESIGN: This retrospective cohort study included 131 gestational diabetes mellitus and 300 non-gestational diabetes mellitus pregnants that were screened and diagnosed between the 24-28 week of gestation. Gestational diabetes mellitus was diagnosed by two-step testing regimen. Anemia in pregnancy was defined as hemoglobin below 11 g/dL in the first trimester. RESULTS: We found out that the mean hemoglobin value and mean corpuscular volume were significantly higher in the gestational diabetes mellitus group (12.2±1.26 vs. 11.72±1.17; p<0.001 and 89.29±7.55 vs. 84.64±6.93; p<0.001). After the analysis of covariance for maternal age, body mass index, parity, birth weight there were significant differences in hemoglobin values and mean corpuscular volume values between two groups (respectively p=0.002, p<0.001). In the gestational diabetes mellitus group >4000 g newborns were significantly higher (19.8% vs.6.7%) (p<0.001). CONCLUSION: We demonstrated that gestational diabetes mellitus was associated with high levels of hemoglobin that was measured in first trimester.